Direct and inverse problems for generalized Pick matrix - Nudelman, A. A. (Methods of Functional Analysis and Topology, 2010)
All matrix modifications of classical Nevanlinna-Pick interpolation problem with a finite number of nonreal nodes which can be investigated by V. P. Potapov method are described.